Mindfulness and mental health: the importance of a clinical intervention to prevent the effects of a traumatic event. A pilot study - Caldiroli, Cristina Liviana; Procaccia, Rossella; Negri, Attà; Mangiatordi, Andrea; Sarandacchi, Silvia; Antonietti, Alessandro; Castiglioni, Marco (Frontiers in Psychology, 2024)
Numerous research studies show that mindfulness can mitigate the negative impact of trauma on mental health by reducing symptoms of anxiety, mediating the relationship between trauma exposure and mental health, and treating symptoms resulting from traumatic events. During the Covid-19 pandemic, which was considered a traumatic event, the well-being of adults and children was severely compromised. Although children seem less vulnerable to the physical effects of the virus, this does not seem to be true for the psychological effects. Indeed, a prolonged period of loss of family activities and routines can have a negative impact on the mental health of children and adolescents. To investigate how mindfulness can help preschool children cope with the effects of Covid-19, a study was conducted on 46 children aged 4-5 years. The programme, based on the work of Jon Kabat-Zinn and adapted to the age of the participants, consisted of eight weekly 45-minute sessions. Qualitative and quantitative results showed positive feedback, indicating that mindfulness helps children make sense of their experiences and achieve functional post-traumatic growth. This approach is seen as a challenge to guide children towards the restoration of psychological well-being, which is essential for good psychological balance.